Dividend policy determinants: a study on the relationship between the financial decision and investment decision of the Malaysian listed companies / Roszilah Shamsuddin - Shamsuddin, Roszilah (2001)
This research reports on the findings of a study that examined the relationship between investment and dividend policy decisions. A sample of 129 companies listed on the main board of KLSE was obtained in order to ascertain this objective. This study automatically helps to find out the factors that influence the dividend payout by examining the interaction between the dividend and investment policies. The Correlation and Regression Analysis are used to analyse the accounting data for the period 1990 until 1994, which obtained from the Corporate Handbook Malaysia. The findings indicate that the relationship does exist between investment and dividend policy decisions, which is negative relationship. The variables such as Net Organizational Capital, Agency Cost and Transaction Cost are significant in determining the factors influence firm's dividend payout. The results indicate that firms will pay a lower dividend payout in order to satisfy the implicit claims of non-investor shareholders. However, firms will pay a higher dividend payout when the free cash flow is larger. Lastly, in order to avoid external financing, firms need to keep dividend payout lower.